1997
DOI: 10.1002/bies.950190410
|View full text |Cite
|
Sign up to set email alerts
|

Insulin second messengers

Abstract: The molecular pathways for insulin's signal transduction from its cell surface receptor to the cell's interior metabolic machinery remain in many ways uncharted. Lately two molecules have been proposed as second messengers transducing the insulin signal into the target cell. One is a phospho-oligosaccharide/inositolphosphoglycan and the other is diacylglycerol, both deriving from the same plasma membrane glycolipid, which is hydrolysed in response to insulin treatment. The phospho-oligosaccharide appears to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 81 publications
0
33
0
Order By: Relevance
“…Sphingomyelin, phosphatidylinositol 4,5, bisphosphate, and GPI proteins/lipids are substrates for enzymes that release ceramide (82,191), inositol trisphosphate (IP3) (192,193), and inositolphosphoglycans (IPG) (194,195), respectively. Each is produced in caveolae after a specific stimuli.…”
Section: Lipid Signalsmentioning
confidence: 99%
“…Sphingomyelin, phosphatidylinositol 4,5, bisphosphate, and GPI proteins/lipids are substrates for enzymes that release ceramide (82,191), inositol trisphosphate (IP3) (192,193), and inositolphosphoglycans (IPG) (194,195), respectively. Each is produced in caveolae after a specific stimuli.…”
Section: Lipid Signalsmentioning
confidence: 99%
“…Further downstream signaling events may include PI3-kinase, p21 ras and MAP kinase, each involved in a big array of the cellular effects of insulin [8]. However, some effects of insulin have been suggested to be mediated by other signaling pathways, perhaps involving insulin receptor-mediated non-covalent activation of G proteins with subsequent PLC-dependent generation of inositolphosphoglycan (IPG) and DAG [9,10]. Thus, IPG and DAG, with or without the involvement of PKC, have booth been implicated as second messengers of insulin [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, some effects of insulin have been suggested to be mediated by other signaling pathways, perhaps involving insulin receptor-mediated non-covalent activation of G proteins with subsequent PLC-dependent generation of inositolphosphoglycan (IPG) and DAG [9,10]. Thus, IPG and DAG, with or without the involvement of PKC, have booth been implicated as second messengers of insulin [9]. We have previously reported that insulin could stimulate chemokinesis in adherent neutrophils, an effect that was sensitive to inhibitors of PI3 kinase and tyrosine kinases [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Transduction of signal after the binding of insulin-related ligands to receptors results in the classic anabolic effects of insulin (reviewed by Stralfors, 1997). Insulin is also known to be a mitogen (Harvey and Kaye, 1990;Gardner and Kaye, 1991).…”
Section: Discussionmentioning
confidence: 99%